2018
DOI: 10.21714/pretexto.v19i3.4762
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de sucesso na carreira: um estudo com docentes de universidades federais do Rio Grande do Sul

Abstract: Este trabalho está licenciado sob uma Licença Creative Commons Attribution 3.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…In view of these questions, we comment that studies carried out within the scope of public higher education institutions (mentioned in the introduction) indicated that the work of professors encloses vectors that increase QWL, such as: maintaining spaces for creativity and reflection as inherent to all their functions (Maia & Vieira, 2016); envisioning a work scenario with a social sense for professors, with possibilities for recognition and prestige, as well as challenging projects in which responsibility and autonomy are valued (Ruza & Silva, 2016); having a recently revised career plan with a high perception of success, being stronger among those in managerial positions and among professors with a doctorate degree (Moreira, Silva, & Gomes, 2018); having the rewarding character of the teaching-learning relationship and the professor-student interaction; providing continuous opportunities for updating knowledge and technical domains; foreseeing instances of participation by representation among democratic management practices (Ruza & Silva, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In view of these questions, we comment that studies carried out within the scope of public higher education institutions (mentioned in the introduction) indicated that the work of professors encloses vectors that increase QWL, such as: maintaining spaces for creativity and reflection as inherent to all their functions (Maia & Vieira, 2016); envisioning a work scenario with a social sense for professors, with possibilities for recognition and prestige, as well as challenging projects in which responsibility and autonomy are valued (Ruza & Silva, 2016); having a recently revised career plan with a high perception of success, being stronger among those in managerial positions and among professors with a doctorate degree (Moreira, Silva, & Gomes, 2018); having the rewarding character of the teaching-learning relationship and the professor-student interaction; providing continuous opportunities for updating knowledge and technical domains; foreseeing instances of participation by representation among democratic management practices (Ruza & Silva, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Teleworking has its advantages and disadvantages (BARROS; SILVA, 2010; CERIBELI; ROCHA, 2019), and the characteristics of this type of work have affected women's lives and careers, owing to personal, organizational, and social mechanisms (O'NEIL, 2003;O'NEIL;BILIMORIA, 2005;LOMBARDI, 2006;MOREIRA et al, 2018). Among these mechanisms are the balance between personal and professional life and job satisfaction (GREENHAUS et al, 2003), the double workload related to employment and housework (BERLATO; CORRÊA, 2017), and the triple workload related to employment, maternity/family, and education/ training.…”
Section: Introductionmentioning
confidence: 99%
“…As mudanças do mundo contemporâneo fizeram reconhecer o indivíduo como um diferencial competitivo (LIMA; ROWE, 2019), isso porque o capital humano é um ativo valioso a ser desenvolvido, que pode viabilizar os ganhos da empresa (BOOG;CASTRO, 2002), seu desenvolvimento e possiblidade de competir no mercado atual (SANTOS, 2019). Quando num ambiente de trabalho satisfatório para ambosfuncionários e chefes -, geralmente a percepção de sucesso profissional é maior (MOREIRA;SILVA;GOMES, 2018).…”
Section: Introductionunclassified